2005
DOI: 10.1029/2004ja010615
|View full text |Cite
|
Sign up to set email alerts
|

Meaning of ionospheric Joule heating

Abstract: [1] The possibility of relating the electric current in the ionosphere to the electric field in the frame of reference either of the neutral atmosphere (as commonly done) or of the plasma raises the question: which should be used in calculating Joule heating? The energy equations for the plasma and for the neutral medium, including collision effects, can be combined with momentum equations to separate energy transfer into work done and heating (this is not the same as separation of energy content into bulk-flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
148
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(153 citation statements)
references
References 9 publications
5
148
0
Order By: Relevance
“…The generalized Ohm's law (see Vasyliūnas and Song, 2005, and references therein for a more detailed discussion) is still well approximated by Eq. (59); only at altitudes below ∼100 km do electron collision terms become important.…”
Section: Pedersen and Hall Currentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The generalized Ohm's law (see Vasyliūnas and Song, 2005, and references therein for a more detailed discussion) is still well approximated by Eq. (59); only at altitudes below ∼100 km do electron collision terms become important.…”
Section: Pedersen and Hall Currentsmentioning
confidence: 99%
“…(59) and Eq. (68) with ∂V /∂t=0 may be combined to eliminate V and express J as a linear function of E+V n ×B/c, with Pedersen and Hall conductivities -the conventional ionospheric Ohm's law (see Song et al (2001) and Vasyliūnas and Song (2005) for critical discussions of its derivation and meaning). The actual approach to steady state is somewhat more complicated than the preceding sketch suggests.…”
mentioning
confidence: 99%
“…The first is heating, both by direct heat flux from the magnetosphere (in the form of chargedparticle precipitation) and by dissipation resulting from electrodynamic processes. The latter is commonly referred to as "ionospheric Joule heating" but Vasyliūnas and Song (2005) have shown that it is, for the most part, collisional frictional heating from the relative motion of plasma and neutrals; the conventionally used expression J · E+V (n) ×B/c does, however, represent the total dissipation rate, about half of which goes into the neutral medium. The second process is acceleration of neutral flow by ion drag (e.g.…”
Section: Magnetospheric Perturbations Of the Neutral Atmospherementioning
confidence: 99%
“…At the same time, the relative motion between neutrals and ionized particles will cause frictional (or Joule) heating Vasyliunas and Song, 2005), which complement thermal drivers caused by solar EUV heating and energetic particle precipitation. The coupled M-I-T system will adjust the various driving processes to result in the plasma convection and thermospheric wind pattern, which we observe.…”
Section: Introductionmentioning
confidence: 99%